The Social and Economic Impact of Philippine International Labor Migration and Remittances - Aniceto Jr. C. Orbeta; Victorina Zosa (Philippine Institute for Development Studies (PIDS), 2009)
The purpose of the paper was to summarize studies identifying the causes and effects of Philippine international labor migration and remittances and to highlight research gaps. Literature and reliability of findings that explore the many facets and implications of the social and economic impacts of international labor migration and remittances were assessed and reviewed. Impacts on education, health, family cohesion, fertility, and demographic distributions, as well as on consumption and investment, and poverty and inequality, were highlighted. The paper argued that understanding the social and economic impact of international labor migration and remittances is complex and an interdisciplinary research is needed to appropriately define the scope of its impact. To move our understanding of the issues forward, in-depth analyses using better specifications, estimation procedures, and data are necessary.
Keywords: J61; 330; Philippines; international labor migration; social and economic impact; Arbeitsmigranten; Rücküberweisungen; Soziale Folgen; Wirkungsanalyse; Philippinen